Ministry of Trade and Industry Decree No. 298 for the Year 2021 Amending Certain Provisions of the Executive Regulations of the Law on Facilitating the Procedures of Granting Licenses for the Industrial Establishments Promulgated by Decree of the Minister of Trade and Industry No. 1082 of the Year 2017 = وزارة التجارة والصناعة قرار رقم 298 لسنة 2021 بتعديل بعض أحكام اللائحة التنفيذية لقانون تيسير إجراءات منح تراخيص المنشآت الصناعية الصادرة بقرار وزير التجارة والصناعة رقم 1082 لسنة 2017 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic